(untitled) (Journal of Patan Academy of Health Sciences, 2015)
A 26 years woman with G3P2L0AO at 40 weeks and 6 days of gestation, but no antenatal clinic visit history presented to Gynecology and Obstetrics out patient clinic complaining decreased feeling of fetal movement since 2 days. Ultrasonography examination revealed fetal demise with amniotic fluid volume of 28 cm. Emergency lower segment caesarean section for ante partum hemorrhage was done. A vertical rupture of the posterior aspect of the uterus from fundus upto the level of cervix with hemoperitoneum of two liters was detected. A macerated dead fetus weighing 3.5 Kg was lying in the peritoneal cavity and the placenta was already partially separated. The mother after hysterectomy was treated in ICU for two days with antihyperglycemic agent additionally and discharged. Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):46-48